AKTIVITAS ANTIBAKTERI EKSTRAK FERMENTAT ISOLAT FUNGI ENDOFIT DARI RIMPANG KUNYIT HITAM (Curcuma caesia Roxb.) TERHADAP BAKTERI INFEKSI MULUT DENGAN METODE DIFUSI AGAR - Bantulu, Ananta Rahayu; Naid, Tadjuddin; Herwin, Herwin (Fakultas Farmasi UMI, 2025)
Black Turmeric (Curcuma caesia Roxb.) is a medicinal plant containing bioactive compounds such as flavonoids, alkaloids and phenols which have antibacterial activity. This study aims to determine the antibacterial activity of fermentate extract of endophytic fungi isolates derived from black turmeric rhizomes (Curcuma caesia Roxb.) against bacteria that cause oral infections such as Porphyromonas gingivalis and Streptococcus mutans by agar diffusion. Endophytic fungi isolates were obtained through isolation and purification processes using YGCA and PDA media. A total of 16 isolates were obtained, and 3 selected isolates (IFKH-8 and IFKH-9) showed antibacterial activity after screening tests (antagonistic tests). Macroscopic and microscopic morphological characterization tests were also carried out on selected isolates. Fermentation was carried out dynamically on MYB media for 3, 7, 14, and 21 days. The fermentate extract was evaluated for its antibacterial activity through the agar diffusion method against test bacteria. The results of the antibacterial activity test of ethyl acetate extract of endophytic fungi by diffusion to obtain the largest inhibition zone diameter in the IFKH-9 isolate of 7.27 mm at a concentration of 10% against Porphyromonas gingivalis bacteria and in the IFKH-9 isolate of 7.29 mm at a concentration of 10% against Streptococcus mutans bacteria